Pembelajaran Responsif Gender pada Pendidikan Anak Usia Dini - Ibrohim Ibrohim (Al Aqidah (Jurnal Studi Islam), 2018)
In the global era women are still placed as second human beingsecond (class human) meaning that women are in a position under men so that many women get gender inequality behavior in the public sphere. The forms of injustice are low in the form of access, control and participation of women. Early childhood education is a great place to sow gender responsive learning because the child has a high absorptive capacity in thinking so that what is taught at an early age will be the basis of his upcoming behavior. Thus can minimize injustice between women and men. Gender responsive learning is a learning that takes active involvement between the sexes so that there is no limit between men and women.